2015
DOI: 10.1002/ajhb.22709
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in children with severe health conditions: Causes of admission and mortality in a Pediatric Intensive Care Unit

Abstract: Although more boys were admitted to the PICU, a significantly higher number of girls died. Younger age and higher occurrence of nosocomial infection among girls could explain this finding. More frequent polytraumatic injuries in boys could reflect an increased exposure to risky activities and/or more careless behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
2
17
2
2
Order By: Relevance
“…Neither did they consider possible differences in severity of illness. In a Spanish study of 2 609 PICU patients, Esteban et al revealed higher rates of hospitalisation for boys, and female gender as a risk factor for mortality, after correcting for a number of factors such as inotropic support, etc., all in line with the present study. In contrast with the present study, however, they hypothesised that the younger age and the higher rates of nosocomial infections in the girls could explain the difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither did they consider possible differences in severity of illness. In a Spanish study of 2 609 PICU patients, Esteban et al revealed higher rates of hospitalisation for boys, and female gender as a risk factor for mortality, after correcting for a number of factors such as inotropic support, etc., all in line with the present study. In contrast with the present study, however, they hypothesised that the younger age and the higher rates of nosocomial infections in the girls could explain the difference.…”
Section: Discussionmentioning
confidence: 99%
“…By using a logistic regression model, they did not find race or ethnicity to be a mortality factor but, after correcting for severity of illness, the female gender was found to be a significant factor for mortality, although gender was not in focus in this study. In a single‐centre study of 2 609 PICU patients in Spain, Esteban et al found that female gender was a negative survival factor (odds ratio 1.55, p = 0.033).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we have analyzed the demographic characteristics of a sample of children with severe trauma to determine the type of events causing these injuries, and to measure the contribution of sex and age in each type of injury. A previous study published in 2015 in the same pediatric population indicated that boys suffered more severe trauma events than girls, but we were not able to stratify those injuries into specific causes by sex and age [15]. Thanks to the Hospital Sant Joan de Déu's participation in a trauma registry (TraumCat) that collects hospital based information of severe trauma patients in Catalonia (Spain), we have had access to a detailed database of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…After the univariate analysis of data, a binary logistic forward regression was performed to establish whether sex and age were risk factors for severe trauma. To carry out this analysis, the database of pediatric patients of Esteban et al [15] was used. Girls and neonates were used as the reference group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation